The contended body: the construction of public discourses on women’s body that makes violence possible. A study case in the Italian North East - Perini, Lorenza; Verzola, Miriam (La camera blu. Rivista di studi di genere, 2014)
The present work historically framed the issue of citizenship of women's rights, such as continuing discrimination that continually reproduces itself through the way in which the female body is represented by the media. Stereotypes and prejudices that build the imagination of common sense with respect to the role of women in society reproduce a scenario of extreme